PENGARUH PELAKSANAAN METODE EKSPLORASI TERHADAP MOTIVASI BELAJAR SISWA DI SDN 34 BABA KECAMATAN CENDANA KABUPATEN ENREKANG - Ampry, Evy Segarawati (Pascasarjana Universitas Negeri Makassar, 2018)
The purpose of this study was to determine whether there was an influence of the Exploration Method Implementation on Student Learning Motivation at 34 Baba Elementary School in Cendana Subdistrict, Enrekang Regency. This type of research was pre-experimental. testing of independent and bound variables is carried out on the sample. The design of this study uses a quantitative approach that examines changes in student motivation through exploration method techniques at Baba 34 Public Elementary School. The research design used was one group pretest posstest desing. The technique of collecting data through observation, questionnaire. The data analysis technique uses descriptive analysis, and inferential analysis that creates a normality test, homogeneity test, and hypothesis testing using the T Test. The results of the study showed that there was a positive influence on the method of exposure on the level of student learning motivation in students at 34 Baba Public Elementary School, which meant that the exploration method was carried out so that the level of student motivation in 34 Baba Public Elementary Schools would also increase.